2018
DOI: 10.1103/physrevlett.120.246602
|View full text |Cite
|
Sign up to set email alerts
|

Spin Subdiffusion in the Disordered Hubbard Chain

Abstract: We derive and study an effective spin model that explains the anomalous spin dynamics in the one-dimensional Hubbard model with strong potential disorder. Assuming that charges are localized, we show that spins are delocalized and their subdiffusive transport originates from a singular random distribution of spin exchange interactions. The exponent relevant for the subdiffusion is determined by the Anderson localization length and the density of the electrons. Although the analytical derivations are valid for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 73 publications
7
49
0
Order By: Relevance
“…We see hence that, for ℓ = ℓ(t) given by (28), I 2 (t) = O((log t) 4 t ab 2 ). Adding the contributions of I 1 , I 2 , we conclude that…”
Section: Griffiths Regionsmentioning
confidence: 75%
“…We see hence that, for ℓ = ℓ(t) given by (28), I 2 (t) = O((log t) 4 t ab 2 ). Adding the contributions of I 1 , I 2 , we conclude that…”
Section: Griffiths Regionsmentioning
confidence: 75%
“…It is known that such systems in general exhibit slow dynamics, most notably reflected in subdiffusive trans-port [45,[50][51][52][53][54][55][56][57][60][61][62][63][64], and it was found that slow dynamics is also visible in the spreading of quantum information [65,86], even in the absence of conserved quantities which could be transported [66].…”
Section: Discussionmentioning
confidence: 99%
“…In the vicinity of the MBL transition, the situation is more complicated: At intermediate disorder, where the system still thermalizes, an anomalously slow thermalization [14,[45][46][47][48][49] is found, which was connected to slow, subdiffusive transport [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. The anomalous thermalization is also reflected in a sublinear powerlaw growth ∝ t α of the wave function entanglement entropy [65], even in systems which do not have globally conserved densities [66], suggesting that the generic slow dynamics is a universal precursor of MBL.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the existence of MBL has been found in a few experimental studies [23-28]. Among several characteristic features of strongly disordered systems is unusually slow time evolution of characteristic physical properties [27,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]] that typically emerges as subdiffusive dynamics as a precursor to MBL transition [18,39,[49][50][51][52][53][54].In this Letter we consider the effect of driving (via the constant electric field) on a quantum particle in a random chain coupled to itinerant hard-core bosons (HCB). We note that such a system simulates the propagation of a (single) charge coupled to spin degrees in strongly correlated systems, as e.g., the disordered Hubbard typemodels [44,55,56], being realized in cold-atom experiments [23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…Moreover, the existence of MBL has been found in a few experimental studies [23][24][25][26][27][28]. Among several characteristic features of strongly disordered systems is unusually slow time evolution of characteristic physical properties [27,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] that typically emerges as subdiffusive dynamics as a precursor to MBL transition [18,39,[49][50][51][52][53][54].…”
mentioning
confidence: 99%